Anxiety Sensitivity Prospectively Predicts Posttraumatic Stress Symptoms Following a Campus Shooting. Issue 3 (May 2016) - Boffa, Joseph W.; Norr, Aaron M.; Raines, Amanda M.; Albanese, Brian J.; Short, Nicole A.; Schmidt, Norman B.
Abstract: Anxiety sensitivity (AS), the feared consequences of anxious arousal, is known to be related to posttraumatic stress symptoms (PTSS) concurrently and longitudinally. However, no studies have demonstrated whether AS prior to a Criterion A traumatic event predicts later PTSS. The present study evaluated whether preshooting AS predicted PTSS following a campus shooting, as well as whether preshooting AS interacted with shooting exposure to predict PTSS. Participants comprised undergraduates ( N = 71) who completed a self-report battery upon enrolling in Introductory Psychology. After a campus shooting later in the semester, they were invited to complete measures of PTSS and level of exposure to the shooting. Preshooting levels of AS significantly predicted PTSS after the shooting. This effect was qualified by a significant AS by shooting exposure interaction, such that those with high AS who were exposed to the shooting reported the greatest levels of PTSS. Though all three of the preshooting physical, cognitive, and social AS subfactors demonstrated main effects significantly predicting postshooting PTSS, only AS physical concerns significantly interacted with shooting exposure. The implications of this study concerning AS as a causal risk factor for PTSD are discussed. Study Highlights: Anxiety sensitivity (AS) was measured in undergraduates prior to a campus shooting. Students were surveyed regarding their exposure to the shooting and PTSD symptoms. Pre-shooting total AS, and all lower-order AS subfactors, predicted PTSD symptoms. High AS and shooting exposure interacted to predict the most PTSD symptoms. Our study is first to demonstrate this relationship in a Criterion A traumatic event.